ANALISIS KINERJA KEUANGAN MENGGUNAKAN WORKING CAPITAL TURN OVER, INVENTORY TURN OVER DAN METODE ECONOMIC VALUE ADDED PADA PT. SEKAR BUMI TBK DAN PT. SIANTAR TOP, TBK - Nur Ali Syah; Alwi Alwi (Eqien - Jurnal Ekonomi dan Bisnis, 2022)
This study aims to determine the financial performance of PT. Sekar Makmur, Tbk and PT. Siantar Top, Tbk based on the Working Capital Turn Over Ratio method, Inventory Turn Over and Economic Value Added (EVA) method for the period 2011-2020. The type of data analysis used in this study is a quantitative descriptive technique. The research population which is also the sample of this study is the financial statements consisting of balance sheets and income statements for the period 2011-2020. Data was collected using documentation techniques, then analyzed by the ratio of Working Capital Turn Over, Inventory Turn Over and analysis using the Economic Value Added (EVA) method consisting of NOPAT, Invested Capital, WACC, Capital Charges analysis. The results of this study that the ratio of the financial performance of PT. Sekar Makmur, Tbk and PT. Siantar Top, Tbk using the Working Capital Turn Over ratio is said to be good and effective because it reaches the average industry standard. Financial performance of PT. Sekar Bumi Tbk and PT. Sekar Bumi Tbk using Inventory Turn Over is said to be less good because it does not reach the industry standard average. While the financial performance of PT. Sekar Bumi Tbk and PT. Siantar Top, Tbk using the Economic Value Added (EVA) method has a negative value (EVA > 0) which means the company's financial performance can be said to be not good in that period, this shows that the company has not succeeded in creating added value for the company and shareholders. The situation of EVA which produces a negative value (EVA < 0) is caused by changes in the value of NOPAT and the value of capital charges where the value of NOPAT is smaller than the value of capital charges. The small value of NOPAT is caused by a decrease in company profits and an increase in the company's interest expense.